2022
DOI: 10.5603/cj.a2022.0013
|View full text |Cite
|
Sign up to set email alerts
|

Cardiac allograft vasculopathy in a long-term follow-up after heart transplantation: Role of remnant cholesterol in residual inflammation

Abstract: Background Cardiac allograft vasculopathy (CAV) is a major prognosis limiting factor in heart transplantation (HTx). Disease development and progression are influenced by multiple determinants, but the role of remnant cholesterol (RC) in CAV has not yet been investigated. Therefore, the present study aimed to assess the prevalence of CAV in a very long-term follow-up after orthotopic HTx and to examine the role of RC in residual inflammation despite secondary prevention. Methods … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
4
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 6 publications
(6 citation statements)
references
References 23 publications
(28 reference statements)
1
4
1
Order By: Relevance
“…CAV is common in long-term follow-up after OHT and may have prognostic implications. [ 13 , 14 ] In contrast to previous reports on the potential of DZ to reduce its progression in short-term follow-up, we found no association between DZ prescription and CAV prevalence. [ 5 ] However, CAV was diagnosed significantly earlier following transplantation in patients not receiving DZ.…”
Section: Discussioncontrasting
confidence: 99%
“…CAV is common in long-term follow-up after OHT and may have prognostic implications. [ 13 , 14 ] In contrast to previous reports on the potential of DZ to reduce its progression in short-term follow-up, we found no association between DZ prescription and CAV prevalence. [ 5 ] However, CAV was diagnosed significantly earlier following transplantation in patients not receiving DZ.…”
Section: Discussioncontrasting
confidence: 99%
“…We found that the preinflammatory state played a mediating role in the relationship between RC and CKD, which is consistent with previous findings of the related inflammatory potential of RC in atherosclerosis [ 25 , 44 , 45 ]. The mediation suggested that RC may cause structural and functional abnormalities of the kidney through renal tissue or systematic inflammation, inducing glomerulosclerosis, renal interstitial damage, and subsequent kidney function decline [ 8 ].…”
Section: Discussionsupporting
confidence: 92%
“…In addition, Wadström and his colleagues studied 106,937 individuals from the Copenhagen General Population Study and 13,974 individuals from the Copenhagen City Heart Study and found that elevated RC was associated with an approximately 5-fold increased risk of peripheral artery disease, 3-fold increased risk of ischemic heart disease and 2-fold increased risk of ischemic stroke ( 9 ). Other investigations also demonstrated the relationship between elevated RC and a higher risk of aortic valve stenosis, cardiac allograft vasculopathy, non-alcoholic fatty liver disease, diabetic nephropathy and chronic kidney disease ( 10 , 19 22 ). To the best of our knowledge, we are the first to report the association between elevated RC and the higher risk of HF in the general population.…”
Section: Discussionmentioning
confidence: 91%